Husbandry Techniques of Lepidochlys olivacea at Raksa Bintana Sea Turtle Conservation, Indonesia - Yusup, Maulid Wahid; Amiin, Muhammad Kholiqul; Nainggolan, Demsiana (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Currently, the threat to sea turtle conservation is still quite high both by natural and anthropogenic (human) factors. Therefore, we try to make efforts in sea turtle conservation, through transferring sea turtle eggs to a semi-natural nest. Subsequently, the rearing of hatchlings that successfully hatched from semi-natural nests. Based on these factors, it is important for us to know how to preserve Lepidochlys olivacea and to analyze the physical and chemical parameters of hatchling rearing. The method of rearing the sea turtles after hatching at the research site has 3 stages, namely moving the newly hatched baby turtles from semi-natural nests to the rearing tanks, 30-day rearing actions in the holding tanks (feeding, changing water, and checking water quality) and releasing the sea turtles to their natural environment, namely the open sea. From the data that has been taken for 30 days, the average temperature results were found to be 26-28oC, for salinity data of 22-25 ppm and for DO data of 7.7-7.9. The measured DO data is still under the range of PP 22 of 2021 Appendix VIII concerning the Implementation of Environmental Protection and Management.